Cool museum experience in the relationship with visitors - Blanco, T.; Loureiro, S. M. C. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
Several researchers have studied the impact of atmospheric cues (Loureiro, 2019), of perceived authenticity (Carù et al., 2017; Loureiro, 2019) and of satisfactory museum experiences (Antón et al., 2018) in the willingness of museum visitors to revisit a museum and/or recommend it to others. However, no study has yet assessed the effect of visitors’ perceived museum coolness and the authentic pride they feel after a visit in those revisit and recommendation intentions.